2021
DOI: 10.1177/00219983211004706
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring of mechanical properties of prestressed glass fiber epoxy composites over 12 months after fabrication

Abstract: Fiber prestressing during matrix curing can significantly improve the mechanical properties of fiber-reinforced polymer composites. One primary reason behind this improvement is the generated compressive residual stress within the cured matrix, which impedes cracks initiation and propagation. However, the prestressing force might diminish progressively with time due to the creep of the compressed matrix and the relaxation of the tensioned fiber. As a result, the initial compressive residual stress and the acqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Fancey 18 pointed that exposing elastically prestressed FRP composites to elevated temperatures may exacerbate matrix creep, thereby reducing the residual tensile force within the fiber and hence decreases the compressive residual stress and its beneficial effect. Mohamed et al 39 showed that when prestressed FRP composites stored in room temperature for 60 days after manufacturing, the tensile strength lost about 3% of its initial strength. However, the absolute guaranteed tensile strength of the prestressed rebars after conditioning (923 MPa) is higher than that of the unprestressed rebars (873 MPa).…”
Section: Durability Evaluationmentioning
confidence: 99%
“…Fancey 18 pointed that exposing elastically prestressed FRP composites to elevated temperatures may exacerbate matrix creep, thereby reducing the residual tensile force within the fiber and hence decreases the compressive residual stress and its beneficial effect. Mohamed et al 39 showed that when prestressed FRP composites stored in room temperature for 60 days after manufacturing, the tensile strength lost about 3% of its initial strength. However, the absolute guaranteed tensile strength of the prestressed rebars after conditioning (923 MPa) is higher than that of the unprestressed rebars (873 MPa).…”
Section: Durability Evaluationmentioning
confidence: 99%
“…Although the fibre prestressing technique is promising, its applications depend on the mechanical properties of the prestressed fibres [ 12 , 13 ]. Commonly, EFP is applicable to brittle (elastic) fibres such as carbon fibres and glass fibres [ 14 , 15 , 16 , 17 ], whilst VFP is more suitable for tough fibres such as semi-crystalline thermoplastic fibres [ 18 ]. As for structural applications, it is demonstrated that VPPMCs are superior to EPPMCs in terms of product geometry and longevity [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%